2023
DOI: 10.1097/icl.0000000000001021
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Bandage Contact Lens in Patients Post-ocular Surgeries: A Systematic Literature Review

Yan Zheng,
Chang-Bin Zhai

Abstract: This study systematically reviewed the performance of bandage contact lenses (BCL) such as lotrafilcon A, lotrafilcon B, senofilcon A, balafilcon A, and comfilcon A as postoperative treatment in different ocular surgeries. A systematic search of English and Chinese databases (from inception to December 2021) was conducted for studies reporting the efficacy of BCLs after ocular surgeries. Postoperative symptoms, corneal healing, and visual outcomes were studied. Overall, 38 studies were identified. Bandage cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
(173 reference statements)
0
1
0
Order By: Relevance
“…There are numerous investigations conducted on the influence of silicon hydrogel BCLs, differing in material composition, on the healing process of corneal epithelial wounds as well as postoperative pain and ocular discomfort following PRK. However, there is a paucity of research on the impact of these lenses on visual rehabilitation [32,33]. Razmjoo et al reported that patients who received Senofilcon A contact lenses demonstrated significantly lower levels of pain than those who were fitted with Lotrafilcon A lenses across all three visit days (days 1, 3, and 5) following PRK with alcohol-assisted epithelial debridement; however, there were no significant differences in visual acuity and epithelial defect size between the two groups [33].…”
mentioning
confidence: 99%
“…There are numerous investigations conducted on the influence of silicon hydrogel BCLs, differing in material composition, on the healing process of corneal epithelial wounds as well as postoperative pain and ocular discomfort following PRK. However, there is a paucity of research on the impact of these lenses on visual rehabilitation [32,33]. Razmjoo et al reported that patients who received Senofilcon A contact lenses demonstrated significantly lower levels of pain than those who were fitted with Lotrafilcon A lenses across all three visit days (days 1, 3, and 5) following PRK with alcohol-assisted epithelial debridement; however, there were no significant differences in visual acuity and epithelial defect size between the two groups [33].…”
mentioning
confidence: 99%